A mosaic of phenotypic variation in giant ragweed (Ambrosia trifida): Local‐ and continental‐scale patterns in a range‐expanding agricultural weed. (14th March 2018) - Hovick, Stephen M.; McArdle, Andrea; Harrison, S. Kent; Regnier, Emilie E.
Abstract: Spatial patterns of trait variation across a species' range have implications for population success and evolutionary change potential, particularly in range‐expanding and weedy species that encounter distinct selective pressures at large and small spatial scales simultaneously. We investigated intraspecific trait variation in a common garden experiment with giant ragweed ( Ambrosia trifida ), a highly variable agricultural weed with an expanding geographic range and broad ecological amplitude. Our study included paired populations from agricultural and natural riparian habitats in each of seven regions ranging east to west from the core of the species' distribution in central Ohio to southeastern Minnesota, which is nearer the current invasion front. We observed trait variation across both large‐ and small‐scale putative selective gradients. At large scales, giant ragweed populations from the westernmost locations were nearly four times more fecund and had a nearly 50% increase in reproductive allocation compared to populations from the core. The degree of surface texture on fruits also declined from east to west. Greater fecundity in the west represents a putative trade‐off between fruit size and fruit number across the study region, although no such trade‐off was found across individual plants. This pattern may effectively result in greater propagule pressure closer to the invasion front. At smaller spatial scales, plants from agricultural populations emerged later and were smaller than plants from riparian populations. However, because plants from agricultural populations allocated more biomass to reproduction, total fecundity did not differ across habitats. Our emergence data are consistent with previous observations showing delayed emergence in agricultural compared to natural populations; thus evolutionary change may be predictable as giant ragweed continues spreading into agricultural fields throughout North America. These shifts in life‐history strategy apparently bear no fecundity cost, suggesting that giant ragweed's success can be attributed at least in part to its substantial adaptive potential.